Enhancing Effects on Vacuole-Targeting Fungicidal Activity of Amphotericin B - Ogita, Akira; Fujita, Ken-ichi; Tanaka, Toshio (Frontiers in Microbiology, 2012)
Invasive fungal infections are recognized as major threats to patients with immune depression as well as those with cancer chemotherapy. Amphotericin B (AmB), a classical antifungal agent with a polyene macrolide structure, is widely used for the control of serious fungal infections. However, the clinical use of this antibiotic is limited by the treatment-associated side effects and the appearance of resistant strains. AmB lethality has been generally elucidated by the alteration of plasma membrane ion permeability due to its specific binding to plasma membrane ergosterol. While, the recent studies with Saccharomyces cerevisiae and Candida albicans reveals the vacuole disruptive action as another cause of AmB lethality on the basis of its marked amplification in combination with allicin, an allyl sulfur compound from garlic. Indeed, AmB causes a serious structural damage to the vacuole membrane at a lethal concentration, and even at a non-lethal concentration in combination with allicin. Such an enhancement effect of allicin is dependent on an inhibition of ergosterol-trafficking from the plasma membrane to the vacuole membrane, which is considered to be a cellular response to protect against the vacuole membrane disintegration. Allicin can also decrease the minimum fungicidal concentration of AmB against the pathogenic fungi C. albicans and Aspergillus fumigatus, as is the case of S. cerevisiae. The synergistic fungicidal activities of AmB and allicin may have significant implications in the development of the vacuole-targeting chemotherapy against fungal infections.